Corrosion Behavior of in-Situ AlB2/Al-Cu Metal Matrix Composite - Elcicek, H.; Savas, O.; Aydin, Z.; Ozdemir, O. K.; Kayikci, R. (POLISH ACAD SCIENCES INST PHYSICS, 2016)
The aim of this study was to fabricate 30 wt.% AlB2/Al-Cu composites using in-situ casting processes and to investigate the corrosion behavior of the composites and of the matrix material in various media. The electrochemical parameters were obtained from potentiodynamic polarization curves. The composites were prepared by liquid reaction of aluminum matrix with boron oxide at 1400 degrees C. The results show that the corrosion resistance of the composite was higher than that of the matrix in selected corrosion media. The anodic corrosion current density values were decreased by reinforcing AlB2 particles.
Keywords: WEAR BEHAVIOR; ALB2; REINFORCEMENT; OPTIMIZATION; Physics